Coupling of 10-methacryloyloxydecyldihydrogenphosphate to tetragonal zirconia: Effect of pH reaction conditions on coordinate bonding. Issue 10 (October 2015) - Xie, Haifeng; Tay, Franklin R.; Zhang, Feimin; Lu, Yi; Shen, Shuping; Chen, Chen
Graphical abstract